Approaches to sustainable forest management - Putz, F.E. (1995)
Claims of sustainability are virtually impossible to prove but enough is known about tropical forest ecology and silviculture to protect ecosystem functions and maintain biodiversity while still deriving financial profits from logging. Rapid improvements in long-term forest production will derive from better planning of harvesting operations and stand improvement treatments. Lack of good management plans generally results in logging practices that destroy natural regeneration and increase forest susceptibility to soil loss, wildfires, and weed infestations. Participation of forest managers, timber importers, researchers, and environmentalists in the development of methods for assessing the social and ecological impacts of tropical forestry operations inspires hope for sustainability.